2016
DOI: 10.1002/ffj.3341
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, odour characteristics and antibacterial activities of the stereoisomeric forms of whisky lactone and its thiono analogues

Abstract: Four stereoisomers of whisky lactone were selectively synthesized in over 99% enantiomeric excess using an amino acid derivative as a resolving agent. Cbz‐L‐proline was the most effective resolving agent, and both trans‐ and cis‐stereoisomers were comparatively easily separated. Odour characteristics of whisky thionolactone were different among four stereomeric isomers, and only (3S,4R)‐whisky thionolactone had mushroom and cis‐jasmone like note. Among all isomers, only (3R,4S)‐whisky lactone showed antibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Originally, whiskey (oak) lactone was identified as cis - and trans -5-n-butyl-4-methyl-4,5-dihydro-2(3H)-furanone in burbon whiskey [ 42 ]. Whiskey lactone molecule has four stereoisomers, but only trans -(3S,4R)-and cis -(3S,4S)-whiskey lactones are naturally occurring [ 43 ]. Although cis -stereoisomer has a lower odor threshold, both cis - and trans -whiskey lactones contribute to fresh wood and coconut aroma of wines [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Originally, whiskey (oak) lactone was identified as cis - and trans -5-n-butyl-4-methyl-4,5-dihydro-2(3H)-furanone in burbon whiskey [ 42 ]. Whiskey lactone molecule has four stereoisomers, but only trans -(3S,4R)-and cis -(3S,4S)-whiskey lactones are naturally occurring [ 43 ]. Although cis -stereoisomer has a lower odor threshold, both cis - and trans -whiskey lactones contribute to fresh wood and coconut aroma of wines [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…5-Acetoxyalkanethioamide analogues (1 and 2) and 5-hydroxyalkanethioamide analogues (3 and 4) with high antibacterial activities were converted to the corresponding optically active forms (Scheme 2). We have previously reported the diastereomeric resolution of various amide compounds using amino acid derivatives as resolving agents [9,32]. We found that Cbz-L-proline is an efficient resolving agent to obtain both the diastereomeric esters with high diastereomeric excesses.…”
Section: Diastereomeric Resolution Of Racemic 5-hydroxyalkanethioamidmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Lactone stereoisomers possess varying odour characteristics and thresholds. [14][15][16] However, there exists a lack of information regarding the odour characteristics and thresholds for the stereoisomeric forms of cognac lactone.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 For whisky lactone, we have reported that only the (3R,4S)-stereoisomer exhibits antibacterial activity against Staphylococcus aureus. 16 Many researchers have attempted to synthesize optically active cognac lactones using methods such as chiral pool synthesis, 4 enzymatic kinetic resolution, 1,20,21 the stereoselective Michael reaction, 22,23 asymmetric cyclopropanation, 24 and organocatalytic α-aminoxylation 25 and β-chlorination. 26 However, diastereomeric resolution remains a widely used technique for the preparation of optically active substances because it is inexpensive and is suitable for large-scale production.…”
Section: Introductionmentioning
confidence: 99%